Development of Interactive Module Based on Realistic Mathematics Education for the Material of Numbers - Haqqi Hidayatullah; Rooselyna Ekawati (MATHEdunesa, 2021)
During the Covid 19 pandemic, which required distance or online learning makes learning material difficult for students to understand, especially number material in junior high schools. One of the ways that teachers can use to facilitate students in learning is by taking approaches, one of which is the Realistic Mathematics Education (RME) approach. To support online learning where students can study independently with teacher guidance so that learning media is very important. One of the learning media developed is an interactive module based RME. The purpose of this research is to describe how the process of developing interactive modules based on realistic mathematics education on numbers and how the results of developing interactive modules are measured from the aspects of validity, practicality, and effectiveness as an alternative learning media. This study used research and development methods, the model used in this research was ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were 15 students in grade 7 junior high school. The test results showed that the module is valid with a percentage of 76,13% valid, from teachers 92,49% practical, from students 86,33% practical, and 88,66% effectiveness. The uniqueness of this interactive module is that it has interactive features such as videos, practice questions, and related learning media. Based on the research conducted, the interactive modules can be said to be a good mathematics learning medium.